Sexual dimorphism of estrogen‐sensitized synoviocytes contributes to gender difference in temporomandibular joint osteoarthritis - Xue, Xin‐Tong; Zhang, Ting; Cui, Sheng‐Jie; He, Dan‐Qing; Wang, Xue‐Dong; Yang, Rui‐Li; Liu, Da‐Wei; Liu, Yan; Gan, Ye‐Hua; Kou, Xiao‐Xing; Zhou, Yan‐Heng (Oral diseases, 2018)
Objectives Temporomandibular joint osteoarthritis (TMJOA) is approximately twice as prevalent in women than in men. Synoviocytes are believed to play a critical role in joint inflammation. However, it is unknown whether synoviocytes from different genders possess sexual dimorphisms that contribute to female‐predominant TMJOA. Materials and Methods Freund's complete adjuvant combined with monosodium iodoacetate was used to induce TMJOA in female and male rats. Histologic and radiographic features were used to evaluate TMJOA. The expression of CD68, MCP‐1, iNOS, and IL‐1β was detected by immunohistochemistry and real‐time PCR. Primary fibroblast‐like synoviocytes (FLSs) isolated from the synovial membrane of female and male rats were used for in vitro experiments. Results Female rats showed aggravated TMJOA features as compared to male rats. Increased expression of iNOS and IL‐1β was detected in synovial membrane from female TMJOA rats as compared to male rats. Furthermore, greater amounts of CD68‐positive macrophage infiltration and increased MCP‐1 expression around the synovial membrane were detected in female TMJOA rats compared to males. Primary cultured FLSs from female rats showed higher sensitivity to TNF‐α treatment and recruited increased macrophage migration than male FLSs. More important, ovariectomy (OVX) by ablation in female rats repressed the sensitivity of female FLSs to TNF‐α treatment due to the loss of estrogen production. Blockage of the estrogen receptor repressed estrogen‐potentiated TNF‐α‐induced pro‐inflammatory cytokine expression in OVX‐FLSs. Moreover, the injection of estrogen receptor antagonists relieved the cartilage destruction and bone deterioration of TMJOA in female rats. Conclusion Estrogen‐sensitized synoviocytes in female rats may contribute to gender differences in the incidence and progression of TMJOA.